Actualization of the Government's Role in the Establishment of the Military Environment Anti-Corruption Corps - Feda Rifandhana , Raditya; Angkoso Wahyono , Bambang; Ningtias , Ayu Dian; Budi Laksono , Agung; Isnawaty Sholekhah , Elok Faradina (Universitas Islam Lamongan, 2024)
Abstract The military is part of a special law, so that in the Unitary State of the Republic of Indonesia, often the Military becomes its own attraction to review in terms of actualization of military criminal handling in the field of corruption in the military environment, as well as its own attraction also in the role of the government in the formation of the Anti-Corruption Corps, the government also in Article 10 of the 1945 Constitution so that it is the commander-in-chief in the Indonesian National Army, When seeing and understanding the handling of special criminal cases, namely corruption, often the independent institution of the Corruption Eradication Commission often has wrong procedures in arresting Military soldiers who commit criminal acts of corruption, in this case there needs to be attention and the latest ideas in the formation of the Anti-Corruption Corps within the Military, so that the handling of corruption cases in the military environment does not occur technical errors or errors in Authority procedures. In this study using the type of Normative Juridical research, reviewing applicable laws and regulations relevant to this research, and approaches with legal theory help complete this research.